PEMBENTUKAN KADER RAPID SEBAGAI UPAYA PENCEGAHAN PENYAKIT DEGENERATIF (DIABETES MELLITUS) DI KELURAHAN WONOROMO SURABAYA - -, UMDATUS SOLEHA; -, SITI NURJANAH (JURNAL PENGEMBANGAN KOMUNITAS, 2018)
Degenerative diseases can occur to anyone, either because of age and poor lifestyle. Degenerativediseases suffered by many people include hypertension, coronary heart disease, diabetes mellitus,osteoarthritis, osteoporosis etc. Community service activities undertaken in Wonokromo VillageSurabaya has the aim of increasing the role of the community in preventing the occurrence ofdegenerative diseases through the establishment of